Buckling delamination of a rectangular sandwich plate containing inner cracks under biaxial loading - Akbarov, S. D.; Yahnioglu, N.; Tekin, A. (SPRINGER, 2013)
Buckling delamination around interface cracks in a rectangular sandwich plate with isotropic, homogeneous layers under biaxial loading is investigated. The plate contains two embedded rectangular interface cracks whose edges have insignificant initial imperfections. The evolution of the imperfections is examined by utilizing the three-dimensional geometrically nonlinear equations of elasticity theory. To solve the corresponding nonlinear problems, the boundary perturbation method and the 3D FEM is employed. According to an initial imperfection criterion, the critical forces are determined. Numerical results are presented for the case where the material of the core layer is stiffer than those of face layers.
Keywords: buckling delamination; critical buckling force; crack; rectangular sandwich plate; 3D FEM; STABILITY; FRACTURE; ELEMENTS; Mechanics; Materials Science; Polymer Science